2022
DOI: 10.3390/met12030471
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring of Biodegradable Magnesium Alloy Surface with Schiff Base Coating via Electrostatic Spraying for Better Corrosion Resistance

Abstract: In this study, three new Schiff bases were synthesized from paeonol and amino acids to prepare a compound Schiff base coating on the Mg-Zn-Y-Nd alloy (ZE21B alloy) surface by electrostatic spraying, and these three single Schiff base coatings were prepared on the ZE21B alloy as control. The results of SEM and XPS confirmed the successful preparation of the coating. Immersion tests and electrochemical tests showed that both the single coating and the compound coating significantly improved the corrosion resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The outcomes suggested that the PDA/FA coating can be used to modify the medical Mg alloy to improve its performance. In the work by Sheng et al [8], three Schiff bases were synthesized to construct the Schiff base coatings on the Mg-Zn-Y-Nd (ZE21B) surface by electrostatic spraying. The results indicated that both the single coating and the compound coating can reduce the corrosion rate of ZE21B alloy, and the compound coating had a synergistic effect in inhibiting corrosion, thus displaying the best anti-corrosion character.…”
Section: Contributionsmentioning
confidence: 99%
“…The outcomes suggested that the PDA/FA coating can be used to modify the medical Mg alloy to improve its performance. In the work by Sheng et al [8], three Schiff bases were synthesized to construct the Schiff base coatings on the Mg-Zn-Y-Nd (ZE21B) surface by electrostatic spraying. The results indicated that both the single coating and the compound coating can reduce the corrosion rate of ZE21B alloy, and the compound coating had a synergistic effect in inhibiting corrosion, thus displaying the best anti-corrosion character.…”
Section: Contributionsmentioning
confidence: 99%
“…However, due to the long time-consuming process, it is generally not suitable for the preparation of ECM coatings on the surface of small-scale biodegradable devices, such as Mg-base stents. Facing this situation, the spraying method is a good choice, which can complete the preparation of devices' surface coating in just a few minutes [64]. Generally speaking, 3D printing technology can accurately prepare ECM coatings for the surface of devices.…”
Section: Preparation Of Ecmmentioning
confidence: 99%
“…Magnesium alloys, which display excellent properties such as low density and high specific strength, have been widely used in aerospace, automobile, and 3C industries [1][2][3]. However, the application and development of magnesium alloys are limited owing to their poor corrosion resistance, especially in harsh corrosive environments [4,5].…”
Section: Introductionmentioning
confidence: 99%